Clinical and prognostic significance of C-reactive protein in the conditions of stable angina pectoris in combination with chronic obstructive pulmonary disease stage II–III - S. Ya. Dotsenko; О. О. Kraidashenko (Zaporožskij Medicinskij Žurnal)
The aim of the study: to evaluate the clinical and prognostic value of the altered C-reactive protein expression level in functional class II–III stable angina pectoris combined with chronic obstructive pulmonary disease (COPD) stage II–III.